ETIKA BISNIS ISLAM - Aura Tafana; Bayu Andika; Fahira Rizka Olivia Mahyu; Feby Nurhalizah Siregar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Islamic Business Ethics is an important foundation in carrying out economic activities in accordance with Islamic teachings. In a business context, ethics not only includes compliance with sharia law, but also moral values that uphold justice, social responsibility and honesty. Principles such as the prohibition of usury, gharar and fraud are the main guidelines for running an ethical business. In addition, Islamic business ethics emphasizes the importance of integrity and openness in every transaction. In the era of globalization and increasingly fierce competition, the application of Islamic business ethics is becoming increasingly relevant, because it not only contributes to economic development, but also builds reputation and trust in the eyes of consumers and the wider community. Thus, understanding and implementing Islamic business ethics not only benefits individuals and companies, but also society as a whole, creating a more sustainable and fair business environment.